Global economic developments 2001-2003 (ECLAC SantiagoCL)
Analyses selected global economic developments during 2001-2003. Deals with the economic performance in developed and developing economies. Presents the different interpretations of the Argentine crisis. Examines the lessons of the Argentine episode for smaller economies and, more specifically Caribbean countries. Looks at the Monterrey conference and its follow-up actions. Analyses the relationship between the Monterrey Consensus and the development needs of Caribbean economies. Focuses on the Doha ministerial conference follow-up and the current state of the trade negotiations between Central America and the United States.
Keywords: ECONOMIC DEVELOPMENT